Relasi Agama Dan Negara (Perspektif Pemikiran Islam) - Gunawan, Edi (Fakultas Adab dan Humaniora UIN Alauddin, 2014)
The relations between religion and state in Islamic thought gives the principle of forming a state such as khalÄ«fah, dawlah, or hukÅ«mah. There are three paradigms of states in Islamic, they are; integrative paradigm, symbiotic paradigm, and secularistic paradigm. In this case, Islam emphasizes democratic values about truth and justice. This democracy can create a good political state. Therefore, this democracy concept is really prefereable in Islam, because Islam is the religion which sets out the truth values and justice. The relation of religion and human right in Islam thought has been determined, because both of these aspects have been built in by all mankind since they were born. Therefore, Islam always emphasizes about the importance of human rights that must be highly appreciated in every states. Â Â